Monitoring changes in seismic velocity related to an ongoing rapid inflation event at Okmok volcano, Alaska. Issue 8 (18th August 2015) - Bennington, Ninfa L.; Haney, Matthew; De Angelis, Silvio; Thurber, Clifford H.; Freymueller, Jeffrey
Abstract Okmok is one of the most active volcanoes in the Aleutian Arc. In an effort to improve our ability to detect precursory activity leading to eruption at Okmok, we monitor a recent, and possibly ongoing, GPS‐inferred rapid inflation event at the volcano using ambient noise interferometry (ANI). Applying this method, we identify changes in seismic velocity outside of Okmok's caldera, which are related to the hydrologic cycle. Within the caldera, we observe decreases in seismic velocity that are associated with the GPS‐inferred rapid inflation event. We also determine temporal changes in waveform decorrelation and show a continual increase in decorrelation rate over the time associated with the rapid inflation event. The magnitude of relative velocity decreases and decorrelation rate increases are comparable to previous studies at Piton de la Fournaise that associate such changes with increased production of volatiles and/or magmatic intrusion within the magma reservoir and associated opening of fractures and/or fissures. Notably, the largest decrease in relative velocity occurs along the intrastation path passing nearest to the center of the caldera. This observation, along with equal amplitude relative velocity decreases revealed via analysis of intracaldera autocorrelations, suggests that the inflation source may be located approximately within the center of the caldera and represent recharge of shallow magma storage in this location. Importantly, there is a relative absence of seismicity associated with this and previous rapid inflation events at Okmok. Thus, these ANI results are the first seismic evidence of such rapid inflation at the volcano.